Spirituality and subjective well-being of Ghanaian parents of children with special needs: The mediating role of resilience - Dey, N.E.W.; Amponsah, B.; Wiafe-Akenteng, C.B. (Sage, 2021)
The study explored the mediating role of resilience in the relationship between spirituality and subjective well-being of 107 Ghanaian biological parents raising children with special needs. Results from mediational analyses revealed that spirituality indirectly influenced life satisfaction, positive affect and negative affect through resilience. Specifically, greater levels of spirituality predicted greater resilience, which successively led to greater life satisfaction, greater positive affect and reduced negative affect. These findings emphasize the necessity of targeting parents’ well-being through resilience to help them deal with the burden of providing care for their children with special needs.
Research Article
Keywords: Ghana; life satisfaction; mediation modelling; negative affect; parents of children with special needs; positive affect; resilience; spirituality; subjective well-being